(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2023)
The phenomenon of population aging, in the light of current demographic changes, constitutes an achievement of undoubted value for any nation, but it is also a challenge in terms of the implementation of mechanisms and strategies that promote active aging in the elderly. This article aims to analyze the concepts of population aging and active aging, with emphasis on the importance that currently revert from the socio-cultural point of view, in view of the imminent growth of this sector of the population. Analytical-synthetic, historical-logical and inductive-deductive methods were used. The analysis provides a vision of the process aimed at achieving in the elderly a well-being not only from the health, but also in the broadest sense, to promote independence, mobility, as well as facilitating jobs that are a continuity of what has been its previous life, which is transformed into social and cultural benefits for society.